2020
DOI: 10.3390/jcm9113611
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inflammatory Markers RANK, MMP-9 and PTHrP in Chronic Apical Periodontitis from People Living with HIV Undergoing Antiretroviral Therapy

Abstract: To compare the expression of the receptor activator of nuclear factor-kappa B (RANK), matrix metalloproteinase 9 (MMP-9) and parathyroid hormone-related protein (PTHrP) in primary chronic apical periodontitis lesions (CAPLs) between people living with HIV (PLWHIV) undergoing antiretroviral therapy (ART) and HIV- individuals, 32 CAPLs (16 lesions from each group) were submitted to histopathological and immunohistochemical analyses and compared between groups. The majority of the PLWHIV group had undetectable pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…MMP-9 is a gelatinase functioning in acute and chronic inflammatory diseases. During the periapical inflammatory process, the expression of MMP-9 is significantly higher than that in normal tissues [ 42 , 43 ], possibly explaining why there were more periapical mineralized tissues and neovascularization of the EndoREZ + MNP + DMADDM group in the histologic images because the expression of MMP-9 was present in osteoclasts and related to the number of neutrophils in inflammatory zones [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is a gelatinase functioning in acute and chronic inflammatory diseases. During the periapical inflammatory process, the expression of MMP-9 is significantly higher than that in normal tissues [ 42 , 43 ], possibly explaining why there were more periapical mineralized tissues and neovascularization of the EndoREZ + MNP + DMADDM group in the histologic images because the expression of MMP-9 was present in osteoclasts and related to the number of neutrophils in inflammatory zones [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A paracrine positive regulator of RANKL signalling in MEC, the parathyroid-hormone-related protein (PTHrP), is usually expressed in keratinocytes of the skin. Since PTHrP is known as an inflammatory marker [ 195 ], keratinocytes from MEC express more PTHrP than normal keratinocytes [ 196 ]. Most recently a study demonstrated, that not only protein expression of PTHrP in MEC epithelium is significantly increased but also positively correlated with the expression of RANKL in osteoblasts [ 197 ] and correlated to the degree of bone resorption [ 191 ].…”
Section: Applicable Targets In Precision Medicine For Mec Therapymentioning
confidence: 99%
“…Osteoporosis, a metabolic skeletal disease reflected by decreased bone mineral density, microarchitectural deterioration, and impaired bone strength, leads to an increased risk of fragility fracture. The development of osteoporosis and bone diseases is influenced significantly by aging, estrogen deficiency, and inflammation [3][4][5]. The fundamental etiology of osteoporosis involves an imbalance in bone turnover, characterized by a higher rate of bone resorption mediated by osteoclasts compared to the rate of bone formation mediated by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%